Effect of grape and rootstock on the assimilation of soil ions in Cuauhtémoc, Chihuahua - Sáenz-Pérez, Criseida Alhelí; Ojeda-Barrios, Dámaris Leopoldina; Perez-Leal, Ramona; Macías-Carranza, Víctor; Cabello-Pasini, Alejandro (Revista Mexicana de Ciencias Agrícolas, 2023)
The use of rootstocks in modern viticulture is a common practice to avoid the impact of phylloxera and nematodes on vineyards. However, the use of rootstocks affects the metabolic processes of the plant, including the assimilation of water and ions from the soil. In Mexico, as in other grape-growing countries, the use of rootstocks has become widespread to protect vineyards against harmful microorganisms. Nevertheless, little is known about the impact of rootstock use on the physiology of vine varieties. Therefore, this study aimed to evaluate the effect of rootstocks 110-R, 101-14, 1103-P, and 3309-C on the assimilation of nitrogen, phosphorus, sodium, copper, iron, manganese, and zinc in Merlot, Shiraz, and Cabernet Sauvignon vines from Chihuahua, Mexico. The nitrogen concentration did not vary in relation to the rootstock used or the variety grown. In addition, the concentration of N in vine leaves decreased over time. This is the result of the mobilization of ions to storage areas during the period of foliar senescence. On the other hand, the concentration of phosphorus, sodium, copper, iron, and zinc in the leaves of the varieties and rootstocks studied did not present significant differences. Nonetheless, the concentration of Mn in Merlot leaves was 30% higher in vines with rootstock 1103-P compared to vines with rootstock 3309-C. In this study, it was shown that rootstock impacts ion assimilation in wine grape varieties.